Management of a patient with thalamic-capsular hematoma complicated with perilesional edema: a case report - Gandhi, Richa; Tikariha, Anshu; Dey, Shivani; Ladkhedkar, Pooja (Frontiers in Human Neuroscience, 2025)
The patient is a 45-year-old woman who was rehabilitated from perilesional oedema with a right thalamic-capsular hematoma. Functional dependence and left-sided hemiparesis were noted. There was considerable improvement in mobility, strength and independence after providing holistic physiotherapy that consisted of multimodal sensory stimulation, tone management, and functional training. Recovery was further enhanced with cutting-edge treatments, including intermittent theta burst stimulation. Remarkable improvements were evidenced in muscle strength, cognitive orientation, and functional independence measures over the entire course of treatment. The article illustrates how quickly and effectively crucial oriented physical therapy at the right point can help reach the best benefit outcome by using the case scenario of a thalamic patient.